2015
DOI: 10.1111/liv.12994
|View full text |Cite
|
Sign up to set email alerts
|

Increasing aortic stiffness is predictive of advanced liver fibrosis in patients with type 2 diabetes: the Rio‐T2DM cohort study

Abstract: In T2DM patients with NAFLD, a high or increasing aortic stiffness predicted development of advanced liver fibrosis on TE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
0
27
1
1
Order By: Relevance
“…A previous study included 100 patients with biopsy‐proven NAFLD detected a positive association between cf‐PWV and histological liver fibrosis score . Leite et al also showed that both an elevated (cf‐PWV ≥10 m/s) and continuously increasing cf‐PWV predicted the progression of advanced liver fibrosis. Thicker CIMT also detected an independent association with the presence of significant liver fibrosis assessed using Fibroscan in asymptomatic general population .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A previous study included 100 patients with biopsy‐proven NAFLD detected a positive association between cf‐PWV and histological liver fibrosis score . Leite et al also showed that both an elevated (cf‐PWV ≥10 m/s) and continuously increasing cf‐PWV predicted the progression of advanced liver fibrosis. Thicker CIMT also detected an independent association with the presence of significant liver fibrosis assessed using Fibroscan in asymptomatic general population .…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of NAFLD has dramatically increased in recent years, which is estimated to be approximately 25.2% worldwide and 23.3% in the Chinese population . NAFLD is the most common cause of chronic liver diseases and associated with end‐stage liver failure and hepatocellular carcinoma . Furthermore, NAFLD imposes excess risk of cardiovascular diseases (CVD), the leading cause of poor prognosis among the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], resumed in Table 1 , have evaluated the relationships between NAFLD and arterial stiffness. All studies, except two of them [ 64 , 65 ], had cross-sectional designs, and all confirmed an association between increased arterial stiffness and NAFLD (mainly detected by ultrasonography), independent of other traditional cardiometabolic risk factors. Of note, one of these studies [ 56 ] demonstrated that the association between NAFLD and increased arterial stiffness was already present at adolescence.…”
Section: Aortic Stiffness and Nafldmentioning
confidence: 99%
“…Results from the Rio-T2DM cohort study (n = 291) suggest that the presence of AS contributes substantially to liver fibrosis [14]. NAFLD in its initial form of simple steatosis is a rather benign situation without excess mortality, while NASH with advanced fibrosis increases total mortality by 70%, due to an increase in CVD mortality by nearly 300% [2].…”
mentioning
confidence: 99%